Review of online measurement techniques for chemical composition of atmospheric clusters and sub-20 nm particles - Zhang, Kewei; Xu, Zhengning; Gao, Jian; Xu, Zhuanghao; Wang, Zhibin (Frontiers in Environmental Science, 2022)
The chemical composition of aerosol particles is crucial to understanding their formation and evolution in the atmosphere. However, very limited information is available for the chemical composition of ultrafine particles, particularly for nanoclusters and newly formed particles, due to the lack of valid analytical methods. This work reviews the online measurement techniques for characterizing the chemical composition of atmospheric clusters and sub-20 nm particles. The commonly used instrumentations are divided into two categories: direct techniques based on mass spectrometry and indirect measurement techniques mainly relying on the physical properties (e.g. hygroscopicity and volatility). The advantages of these techniques are compared and their limitations in the lab and field applications are summarized. The combination of direct and indirect techniques is discussed, and this may provide more comprehensive understanding of chemical information of atmospheric clusters and particles. We propose that the newly developing instrumentations are needed to improve the collection efficiency for direct techniques, or the chemical resolution for indirect techniques. Future development should focus on obtaining simultaneous measurements of particle physical and chemical properties, which can be helpful in improving the accuracy of modeling and the understanding of particle formation and evolution.